Peripheral Blood Mononuclear Cell Gene Expression in Chronic Obstructive Pulmonary Disease: miRNA and mRNA Regulation - Wang L; Zhao H; Raman I; Yan M; Chen Q; Li QZ (Dove Medical Press, 2022)
Lijing Wang,1 Hongjun Zhao,2,* Indu Raman,3 Mei Yan,3 Qiong Chen,1 Quan-Zhen Li3,* 1Departments of Geriatrics, Respiratory Medicine, National Clinical Research Center for Geriatric Disorders, Xiangya Hospital, Central South University, Changsha, 410008, Hunan, People's Republic of China; 2Department of Rheumatology and Immunology, Xiangya Hospital, Central South University, Changsha, 410008, Hunan, People's Republic of China; 3Department of Immunology, University of Texas Southwestern Medical Center, Dallas, TX, 75390, USA*These authors contributed equally to this workCorrespondence: Quan-Zhen Li, Department of Immunology, University of Texas Southwestern Medical Center, 5323 Harry Hines Blvd., Dallas, TX, 75390, USA, Tel +1 214-645-6071, Fax +1 214-645-6074, Email quan.li@utsouthwestern.eduIntroduction: The mechanisms underlying chronic obstructive pulmonary disease (COPD) remain unclear. Genetic and genomic changes may play a significant role in the pathogenesis of COPD. Identification of differentially expressed genes and miRNAs and their regulatory mechanisms at the whole-genome level will provide a comprehensive understanding of the development of COPD.Methods: Peripheral blood mononuclear cells (PBMCs) from 12 patients with COPD and 12 normal controls were examined at the miRNA and mRNA expression levels using Affymetrix GeneChip. Microarray data were analyzed with Affymetrix Transcriptome Analysis Console 2.0 and GeneSpring software. Gene interaction pathways of the differentially expressed genes and miRNA-mRNA regulation were analyzed using the Ingenuity Pathway Analysis software. Four differentially expressed genes and one miRNA were further confirmed using RT-qPCR.Results: One hundred and thirty-three upregulated and 973 downregulated genes were identified in PBMCs of patients with COPD. Pathway analysis on the differentially expressed genes in COPD revealed significant enrichment in IL-8 signaling and iCOS-iCOSL signaling in T helper cells. Seventy-seven upregulated miRNAs and 43 downregulated miRNAs were differentially expressed between PBMCs from patients with COPD and normal controls. Among these 120 differentially expressed miRNAs, 42 miRNAs targeting 28 upregulated genes and 69 miRNAs targeting 498 downregulated genes were identified. The expression of CXCR1, HBEGF, TREM-1, and hsa-miR-148a-3p was more elevated in patients with COPD than in normal controls, whereas NFAT5 was decreased.Conclusion: miRNAs and mRNAs are differentially expressed in PBMCs of patients with COPD, compared with normal controls. miRNAs regulate the expression of mRNAs, and thus play a role in the pathogenesis of COPD. Investigating these relationships may provide further insight into the mechanisms of COPD.Keywords: COPD, whole-genome transcription, gene, miRNA, peripheral blood mononuclear cells